Irrigation systems and social organization in the Colca Valley: Yanque case - Valderrama Fernández, Ricardo (1986)
Until today, little importance has been given to the hydraulic systems of the Andean communities; however, the few studies on this subject show the importance of irrigation of similar characteristics that occur throughout different irrigation farming communities in the Cisandina area. These studies (Mitchell, 1981; Shaedel, 1983; Fonseca, 1983) draw attention to the rational use of irrigation water, according to the ecology of these communities, through which farmers try to optimize their production. Another group of works (Arguedas, 1968; Ossio, 1976; Sherbondy, 1982, 1983) has paid attention to the "festive ceremonies of the cult of water" that are practiced in various Andean communities, in which there is agriculture with irrigation, under different conditions. names "Water Festival or Yaku Raymi", "Clean Acequias or Yarqa Aspiy", "Champerías", etc.; which constitute "one of the most obvious expressions of the impact that irrigation has had on the Andean social organization" (Gelles, 1984:1), for which they have called the attention of several Peruvian and foreign scholars.